CREATING THE JOY OF READING LITERATURE TO BUILD STUDENTS’ CHARACTER ON READING HOBBY - Wijaya, M. Sayid (English Education: Jurnal Tadris Bahasa Inggris, 2014)
Learning to read means learning to open the window of the world. Students with higher frequency of reading will result better comprehension for that they store information more than students with lower frequency of reading. However, to construct students’ awareness to read is a big deal. Most of them said that reading is boring. In this case, developing the joy of reading, especially reading literature works, is a crucial aspect to stimulate students’ reading hobby as one the character values. To develop the joy of reading literature, initially, the teacher needs to design the appropriate classroom activities. After designing the activities, he needs to select suitable materials. Then, the selected activities and materials are applied in the classroom. Additionally, the teacher also designs reading activities for students out of the classroom. The result of the process of designing classroom activities, selecting materials, and its application to the classroom enhances students’ interest in reading literature. Thus, those designs and processes are crucial in stimulating students’ reading hobby. When students enjoy reading literature, their awareness to read is built up. In result, this will stimulate their reading awareness. The more they read, the more knowledge is stored in their memories.